Combined effect of relief and level of expansion in a suddenly expanded flow - Syed, Syed Ashfaq; Khan, Sher Afgha (International Organisation of Scientific Research (IOSR), 2015)
This paper presents the experimental results on the flow characteristics of a suddenly expanded flow from the convergent nozzle for subsonic, sonic and sonic under expanded flow. In the present study micro jets were used to investigate the effect of micro jets on base pressure flow field in the enlarged duct. Accordingly an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The NPRs of the present study are 1.5, 2.0, 2.5 and 3.0 and the area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied were 2.4, 3.61, 4.84, and 6.25. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. From the results, it is seen that the flow in the base region is dominated by the waves, the general perception what we have that correctly expanded flow will be from waves is proved to be wrong; also, it is found that for L/D in the range L/D = 4, 3 and 2 the flow remains oscillatory mostly for NPRs 2.5 and 3.0. However, these oscillations are suppressed either with the increase in the L/D ratio in the range from 3 to 10 or with decrease in the level of expansion NPRs from 2.5 to 1.5. The present study explicitly reveals that, the base pressure in a suddenly expanded axi-symmetric duct can be controlled by employing micro jets under the influence of favorable pressure gradient.